2009
DOI: 10.3109/10739680903164131
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ovariectomy and Estrogen on Penetrating Brain Arterioles and Blood‐Brain Barrier Permeability

Abstract: Objective We investigated the effect of estrogen replacement on the structure and function of penetrating brain arterioles (PA) and blood-brain barrier (BBB) permeability. Methods Female ovariectomized Sprague Dawley rats were replaced with estradiol (E2) and estriol (E3) (OVX+E; N=13) and compared to ovariectomized animals without replacement (OVX; N=14) and intact controls (CTL, proestrous; N=13). Passive and active diameters, percent tone and passive distensibility of pressurized PA were compared. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…The permeability of the BBB may be modulated through both ERα and ERβ (Bake and Sohrabji, 2004; Brown et al, 2010; Cipolla et al, 2009). 17βE2 also plays an important role in mediating leukocyteendothelial interations.…”
Section: Mechanisms Of Estrogen Neuroprotectionmentioning
confidence: 99%
“…The permeability of the BBB may be modulated through both ERα and ERβ (Bake and Sohrabji, 2004; Brown et al, 2010; Cipolla et al, 2009). 17βE2 also plays an important role in mediating leukocyteendothelial interations.…”
Section: Mechanisms Of Estrogen Neuroprotectionmentioning
confidence: 99%
“…Animal studies also support a role of E2 on EC integrity and permeability. Studies have shown that the permeability of the blood brain barrier is 500% greater in ovariectomized (OVX) than intact female rats, and E2 replacement restores barrier properties [57]. The E2-induced decrease in EC permeability may be related to regulation of prostaglandin E2 (PGE2) levels [58].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, however, BBB permeability increased significantly in the ovariectomized ischemic group, and this result is different from the results of the above-cited study. In a study by Cipolla et al (8) estrogen treatment to ovariectomized rats was found to significantly lower the permeability of the blood-brain barrier. Chi et al (7) investigated the effect of 17β-estradiol on BBB permeability during focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%